Associations between spontaneous electroencephalogram oscillations and oxygen saturation across normobaric and hypobaric hypoxia. Issue 6 (30th January 2023) - Hutcheon, Evan A.; Vakorin, Vasily A.; Nunes, Adonay; Ribary, Urs; Ferguson, Sherri; Claydon, Victoria E.; Doesburg, Sam M.
Abstract: High‐altitude indoctrination (HAI) trains individuals to recognize symptoms of hypoxia by simulating high‐altitude conditions using normobaric (NH) or hypobaric (HH) hypoxia. Previous studies suggest that despite equivalent inspired oxygen levels, physiological differences could exist between these conditions. In particular, differences in neurophysiological responses to these conditions are not clear. Our study aimed to investigate correlations between oxygen saturation (SpO2 ) and neural responses in NH and HH. We recorded 5‐min of resting‐state eyes‐open electroencephalogram (EEG) and SpO2 during control, NH, and HH conditions from 13 participants. We applied a multivariate framework to characterize correlations between SpO2 and EEG measures (spectral power and multiscale entropy [MSE]), within each participant and at the group level. Participants were desaturating during the first 150 s of NH versus steadily desaturated in HH. We considered the entire time interval, first and second half intervals, separately. All the conditions were characterized by statistically significant participant‐specific patterns of EEG–SpO2 correlations. However, at the group level, the desaturation period expressed a robust pattern of these correlations across frequencies and brain locations. Specifically, the first 150 s of NH during desaturation differed significantly from the other conditions with negative absolute alpha power–SpO2 correlations and positive MSE–SpO2 correlations. Once steadily desaturated, NH and HH had no significant differences in EEG–SpO2 correlations. Our findings indicate that the desaturating phase of hypoxia is a critical period in HAI courses, which would require developing strategies for mitigating the hypoxic stimulus in a real‐world situation. Abstract : It is still unknown whether there are differences in neurophysiological responses to normobaric and hypobaric hypoxia, as normobaric hypoxia is often used as a proxy for hypobaric hypoxia during research and hypoxia awareness courses. We collected 5‐min of eyes‐open resting‐state data with an electroencephalogram (EEG) and oxygen saturation (SpO2 ) monitor from 13 participants during normobaric hypoxia, hypobaric hypoxia, and normobaric normoxia. We found that there is less variability in the spatiotemporal patterns of EEG–SpO2 correlations during the desaturation phase of normabric hypoxia when compared to a stable desaturated phase.